Development of a damage prediction system for bending and cutting of high strength steels - Vatter, Peter; Hildering, Sven; Tsoupis, Ioannis; Merklein, Marion (Key Engineering Materials, 2013)
The application of modern high-strength low-alloy steels (HSLA) and advanced high strength steels (AHSS) for structural and safety relevant components in the automotive industry offers the advantage of combining low specific weight with high material strength. Typical manufacturing processes for these steel grades are bending and cutting operations. However, the forming and cutting potential of these innovative steel grades is different to conventional steels as the process and the damage behaviour is changing. In bending operations cracks occur at the outer bending edge, whereas in cutting operations delamination can appear at the sheared edge, which can initiate component failure. In the scope of this work a method is presented to describe the damage behaviour of both, bending and cutting operations, by theoretical meta models. In order to generate a database experiments were carried out using a typical HSLA. The main influencing factors have been varied experimentally, such as the rolling direction, normalised bending radius and punch to die clearance. To calculate further sampling points a finite element model has been developed and validated against the experimental data. The damage criterion of LemaÎtre has been applied. The necessary parameters were determined by reverse numerical identification by means of the major strain for the bending operation and by the punch force-punch stroke curve for the cutting operation. To build up a system for the prediction of the damage the gained data basis was approximated by mathematical functions. An error analysis was carried out showing good accordance. In doing so, a meta model for the evaluation of the damage rate could be established. The functions were implemented in a software tool which allows the user to determine the failure probability for a given parameter set. This software tool is exemplarily validated against experimental air bending tests using a higher normalised bending radius. Copyright © 2013 Trans Tech Publications Ltd.
LFT Import::2019-07-29 (1853)
Keywords: Bending; Cutting; Damage prediction; High strength steel